EXPERIENCE OF BODILY PAIN IN THE WORKPLACE AS A SPECIFIC FACTOR FOR THE PROFESSIONAL BURNOUT OF A DOCTOR - Яшникова, Мария Викторовна; Федорова, Лилия Темурхановна; Потеряева, Елена Леонидовна; Смирнова, Елена Леонидовна (Medicine in Kuzbass, 2024)
Professional burnout is a complex interdisciplinary problem at the junction of hygiene, psychology, psychophysiology and physiology, which implies the possibility of the influence of physiological abnormalities on habitual psycho-emotional reactions during the work process. The purpose of the study – to analyze the relationship of working conditions and health status with the professional burnout of a doctor. Material and methods. The study used survey data, regulatory documentation of institutions concerning 346 doctors from medical institutions in Novosibirsk for 2020-2021. The differences between the independent samples were estimated according to the statistics χ2, the significance of the variance difference was estimated according to the Fisher criterion. The nonparametric analysis of the samples was carried out according to the Mann-Whitney criteria and the Wilcoxon T-criterion. Results. The tested harmfulness from the production factors of the environment of medical institutions belongs to the 3rd class of working conditions. 40.5 % of doctors were recognized as healthy according to the PMO statements, while the survey revealed a significant decrease in the health-related quality of life. The statistically significant influence of the factor of experiencing bodily pain in the workplace on the progression of low professional maladjustment from a low to a moderate degree has been determined. Conclusions. 1. The doctor’s health, physical and mental well-being, underlies the specialist’s resistance to the effects of professional stress factors, forming the basis of professional longevity. Modern working conditions of a doctor require a special ergonomic assessment due to the extremely widespread experience of bodily pain in the workplace among doctors. 2. Recurrent or chronic pain syndrome in the workplace has a long-term negative effect on the psycho-emotional status of a doctor when performing work duties.